Eksplorasi Kearifan Lokal Kota Semarang dalam Kerangka R-STEAM (Agama-Sains, Teknologi, Rekayasa, Seni, dan Matematika) - Moh. Fathurrahman; Siti Maryatul Kiptiyah; Novi Setyasto; Nur Indah Wahyuni; Wulan Aulia Azizah (Jurnal Penelitian Pendidikan IPA, 2025)
An exploration of the local wisdom of Semarang City through the R-STEAM (Religion, Science, Technology, Engineering, Arts, and Mathematics) approach shows the integration of local cultural, historical, artistic, and culinary values with the application of R-STEAM to Lawang Sewu, Semarangan batik, and Semarang spring rolls. This study enriches the understanding of science and technology while strengthening cultural awareness and local identity. Lawang Sewu, as a historical building, becomes an ideal model to study mathematics in geometry, as well as the integration of religious values and art in construction. Batik Semarangan represents the application of R-STEAM in the exploration of the art and technology of batik making, including the use of natural dyes and modern engineering techniques for innovative motifs. Finally, Semarang spring rolls within the R-STEAM framework encompass traditional food processing techniques, health and nutrition aspects, and innovative approaches in combining tradition with modern technology in the culinary industry, particularly in relation to healthy food learning. Overall, the application of R-STEAM tools in this exploration of Semarang's local wisdom provides significant opportunities to integrate cultural heritage with science, technology and arts learning. Practical implications include recommendations for educational curriculum development that integrates R-STEAM with local wisdom, as well as the formulation of education policy that supports the preservation and utilization of local culture in the context of modern education